Validation of Nursing Outcome Indicators in Patients with Postsurgical Delirium - Melguizo Herrera, Estela; Manrique Anaya, Yolima; Torres Contreras, Claudia; Rivera Carvajal, Raquel; Hueso Montoro, Cesar (Investigación y Educación en Enfermería, 2024)
Objective. To validate the content of the indicators proposed from the Nursing Outcome Classification in a care plan for delirium management in older adults. Methods. Content validity study, conducted under the expert judgment technique. The procedure was developed in five moments: organization of indicators that respond to the nursing outcome classification for delirium management, support with literature of the indicators that responds to the result, selection of experts, establishment of agreements, and discussion. Quality criteria evaluated: pertinence and relevance, the Content Validity Coefficient and average scores assigned by the experts were calculated. Results. The study had the participation of 14 experts. The indicators, according to criteria of pertinence and relevance evaluated by experts showed a global average content index value of 0.93; 97.05% (66) of the indicators had Content Validity Coefficient > 0.75. Conclusion. The quantitative findings of the indicator validation process showed high relevance and pertinence index, which favors their being applied to measure care changes in patients with delirium.